INFLUENCE OF VARIABLE PRESSURE ON ACOUSTIC AND VOLUMETRIC PROPERTIES OF TERRIGENOUS RESERVOIR ROCKS (ON THE EXAMPLE OF SEMYRENKIVSKA AREA SAMPLES) - Vyzhva, S.; Shynkarenko, A.; Bezrodna, I.; Shchurov, I.; Gafyth, I.; Solodkyi, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Аnalysis and interpretation of investigations of the rock samples from the producing horizons of Semyrenkivska area of Dnieper-Donets Basin under high pressure were carried out. The purpose of this paper is to determine peculiarities of acoustic and volumetric properties of Lower Carboniferous terrigenous rocks changes under high pressure and qualitative evaluation of their void space structure changes during compression and relaxation. Set of samples is presented by Lower Carboniferous sandstones. Petrophysical investigations were carried out at the petrophysical laboratory of Institute of Geology of Taras Shevchenko National university of Kyiv. Research technique includes the measurement of compressional wave velocity and open porosity value of the samples saturated with the reservoir fluid model under the influence of increasing hydrostatic pressure (from 0 up to 60 MPa) and decreasing pressure (from 60 to 0 MPa). Compressional waves' velocities were found to be more sensitive to pressure variations than the open porosity value. The highest changes in these parameters were obtained for the pressure range from 0 to 10-15 MPa. The peculiarities of the void space structure of rocks were qualitatively determined and the groups of samples with similar distribution of the porosity types were separated using the data of the conducted investigations. Qualitative prediction of reservoir properties changes for the horizons B-17, B-18 and B-19 of Semyrenkivska area in case of hydrocarbons extraction or their variable depth based on the analysis of elastic waves and open porosity values changes under the influence of high pressure can be made. Results of the conducted investigations will be used for the acoustic data inversion into the parameters of void space structure and quantitative evaluation of distribution of different pore types in the samples.
Keywords: petrophysics; reservoir rock; void space structure; high-pressure unit; compressional wave velocity; open porosity